Identity and Struggle at the Margins of the Nation-State The Laboring Peoples of Central America and the Hispanic Caribbean - Lauria-Santiago, Aldo; Chomsky, Aviva, 1957- (Book collections on Project MUSE., 1998)
Identity and Struggle at the Margins of the Nation-State brings together new research on the social history of Central America and the Spanish-speaking Caribbean during the late nineteenth and early twentieth centuries. Aviva Chomsky and Aldo A. Lauria Santiago have gathered both well-known and emerging scholars to demonstrate how the actions and ideas of rural workers, peasants, migrants, and women formed an integral part of the growth of the export economies of the era and to examine the underacknowledged impact such groups had on the shaping of national histories.Responding to the fact that the more common, elite-centered "national" histories distort or erase the importance of gender, race, ethnicity, popular consciousness, and identity, contributors to this volume correct this imbalance by moving these previously overlooked issues to the center of historical research and analysis. In so doing, they describe how these marginalized working peoples of the Hispanic Caribbean Basin managed to remain centered on not only class-based issues but on a sense of community, a desire for dignity, and a struggle for access to resources. Individual essays include discussions of plantation justice in Guatemala, highland Indians in Nicaragua, the effects of foreign corporations in Costa Rica, coffee production in El Salvador, banana workers in Honduras, sexuality and working-class feminism in Puerto Rico, the Cuban sugar industry, agrarian reform in the Dominican Republic, and finally, potential directions for future research and historiography on Central America and the Caribbean.This collection will have a wide audience among Caribbeanists and Central Americanists, as well as students of gender studies, and labor, social, Latin American, and agrarian history.Contributors. Patricia Alvarenga, Barry Carr, Julie A. Charlip, Aviva Chomsky, Dario Euraque, Eileen Findlay, Cindy Forster, Jeffrey L. Gould, Lowell Gudmundson, Aldo A. Lauria Santiago, Francisco Scarano, Richard Turits.